Taxonomic review of the subfamily Lohmannellinae (Acari: Trombidiformes: Halacaridae) with morphological comparisons among genera - Abé, Hiroshi (Zootaxa, 2021)
Taxonomic review of the halacarid subfamily Lohmannellinae is carried out with regard to morphology, biology, habitat, geographical distribution, and bibliography. The subfamily is one of 16 subfamilies in the family Halacaridae and consists of five genera, Lohmannella, Porolohmannella, Scaptognathides, Scaptognathus, and Xenohalacarus, which include 38, 1, 11, 31, and 1 known species, respectively. The genera Scaptognathides, Scaptognathus, and Xenohalacarus are marine, Porolohmannella is a freshwater inhabitant, and Lohmannella lives in marine and freshwater. The species in this subfamily are mostly arenicolous and probably carnivorous or omnivorous in feeding habits. As for the geographic distribution, Lohmannella shows almost cosmopolitan distribution; Scaptognathus is also widely distributed except for polar regions. The genus Scaptognathides is distributed more in southern oceans than in the northern circle, and Xenohalacarus is restricted to the Coral Sea. The freshwater genus Porolohmannella has wide inland distribution except for the African, South American, Australian, and Antarctic continents. Based on morphological comparisons among five genera, Scaptognathus is regarded as the most unique taxon and Lohmannella and Porolohmannella as rather conservative taxa in the subfamily.